Implementation of Transform Domain Video Steganography (DCT) Method for Embedding Secret Messages in Video Media - Adri Muliadi Pasaribu; Ikmat Pengertian Hia; Otomosi Gulo (Sean Institute, 2025)
Steganography is a technique for concealing information by embedding a secret message into a digital medium without causing significant visual changes. In this study, a transform-domain-based video steganography method using the Discrete Cosine Transform (DCT) is implemented to embed secret messages into video media. The embedding process is performed on each video frame by dividing the frame into 8×8 pixel blocks, followed by applying DCT to each block. The secret message is converted into a bitstream and embedded by modifying the mid-frequency coefficients in the DCT domain. After the embedding process, inverse DCT is applied to reconstruct the frame back into the spatial domain, resulting in a stego video. The test results show that the visual differences between the stego video and the original video are not significantly perceptible, thus satisfying the imperceptibility aspect of steganography. In addition, the secret message can be successfully extracted with a high level of accuracy, indicating that the proposed method is capable of maintaining a balance between embedding capacity, visual quality, and extraction reliability. Therefore, the transform-domain-based video steganography method using DCT can be effectively used as a solution for embedding secret messages in video media.